The Mechanism, And Some Parameters Controlling, The Water Jet Cutting Of Rock - David A. Summers; Steven McGroarty (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1982)
The last ten years has witnessed the change in water jet cutting studies, on rock, from laboratory testing to prototype use of field equipment. Unfortunately, while equipment and technological developments have occurred, the understanding of the exact mechanisms of water jet erosion have been less well developed. Commonly, theoretical evaluations have used the uniaxial compressive strength of the target rock as the major parameter of rock erosion resistance . It is considered that the structural properties of the rock, and most particularly, the flaw density and heterogeneity of the rock are much more important parameters. This is demonstrated and discussed. Locating the jet and target under water and pressurizing the containing vessel makes it is possible to induce cavitation in and around the water jet and create a much slower erosion process.